AB0282 Adjusting the dose of tofacitinib to achieve optimal results in the management of patients with active rheumatoid arthritis (RA) may offer more successful results than utilising a standard fixed one dose approach. (12th June 2018) - Gaylis, N.; Sagliani, J.; Needell, S.
Abstract : Background: We have previously reported results of patients with active RA who had been unresponsive to tofacitinib at 5 mg bid but who had demonstrated significant response after dose escalation to 10 mg bid. 1 2 This extension trial was performed to see if 9 patients who had failed to reach treatment target on 5 mg bid but then responded to 10 mg bid of tofacitinib would maintain their clinical target if the dose was reduced down to 5 mg bid. Furthermore, if the patients could not maintain their clinical response on the lower dose, we explored whether increasing the dose of tofacitinib up to 10 mg bid could again result in a target response. Objectives: The objectives were as follows: to explore the response of patients who achieved a treatment target when taking 10 mg bid of tofacitinib and then reduced the dose down to 5 mg bid; to report the results of the patients who could not maintain the target response at 5 mg bid and then increased the dose back up to 10 mg bid;and to identify if there was any separation between the clinical and structural findings at 5 mg bid vs 10 mg bid. Methods: Nine RA patients who were unresponsive to treatment with tofacitinib at a dose of 5 mg bid plus MTX (10–25 mg weekly) were dose escalated to 10 mg bid and reached low disease activity (LDA) or remission at the increased dose. These patients were maintained on 10 mg bid of tofacitinib for 6 months and sustained a clinical target of LDA or remission. After 6 months, the dose of tofacitinib was reduced back to 5 mg bid which had previously not been an effective dose. The clinical response was measured by the Clinical Disease Activity Index (CDAI) and the structural response was measured by an MRI of the index hand/wrist and blindly read by a musculoskeletal radiologist using a modified OMERACT-RAMRIS score. If the patients could not maintain their positive clinical response for 3 months the dose of tofacitinib was escalated back up to 10 mg bid. Results: Of the 9 enrolled patients, 6 patients maintained LDA or Remission over the next 6 months once the dose of tofacitinib was reduced back down to 5 mg bid. Three 3 patients were unable to maintain their treatment target at the reduced dose and were dose escalated back up to 10 mg bid at which time they achieved the treatment target.(See table 1) The MRI findings showed no difference in structure at either dose and do not appear to demonstrate a relationship to the clinical findings. There were no clinically significant adverse events in either group. Conclusions: This study confirms the previous findings that 10 mg bid of tofacitinib may be the effective dose needed for some patients with active RA to reach treatment target.( 1 It also suggests that there is an opportunity to reduce the escalated dose back down to the standard dose once a target response is achieved. This in many ways is similar to the clinical use of other drugs used to treat RA including corticosteroids, MTX and biologics where dose adjustment may well increase the therapeutic benefit of the molecule and allow subsequent dose adjustments to maintain efficacy with a lower adverse event profile. Additional studies will be needed to test the results found in this trial. References: [1] Gaylis N, et al. ACR2017. [2] Fleishman R, Kremer J, et al. Internal Journal of Rheum, Dis2016. Disclosure of Interest: None declared